Molecular phylogenetic relationships and phenotypic diversity in miniaturized toadlets, genus Brachycephalus (Amphibia: Anura: Brachycephalidae) - Clemente-Carvalho, Rute B.G.; Klaczko, Julia; Ivan Perez, S.; Alves, Ana C.R. [UNESP]; Haddad, Célio F.B. [UNESP]; Dos Reis, Sérgio F. (Elsevier, 2011)
Toadlets of the genus Brachycephalus are endemic to the Atlantic rainforests of southeastern and southern Brazil. The 14 species currently described have snout-vent lengths less than 18. mm and are thought to have evolved through miniaturization: an evolutionary process leading to an extremely small adult body size. Here, we present the first comprehensive phylogenetic analysis for Brachycephalus, using a multilocus approach based on two nuclear (Rag-1 and Tyr) and three mitochondrial (Cyt b, 12S, and 16S rRNA) gene regions. Phylogenetic relationships were inferred using a partitioned Bayesian analysis of concatenated sequences and the hierarchical Bayesian method (BEST) that estimates species trees based on the multispecies coalescent model. Individual gene trees showed conflict and also varied in resolution. With the exception of the mitochondrial gene tree, no gene tree was completely resolved. The concatenated gene tree was completely resolved and is identical in topology and degree of statistical support to the individual mtDNA gene tree. On the other hand, the BEST species tree showed reduced significant node support relative to the concatenate tree and recovered a basal trichotomy, although some bipartitions were significantly supported at the tips of the species tree. Comparison of the log likelihoods for the concatenated and BEST trees suggests that the method implemented in BEST explains the multilocus data for Brachycephalus better than the Bayesian analysis of concatenated data. Landmark-based geometric morphometrics revealed marked variation in cranial shape between the species of Brachycephalus. In addition, a statistically significant association was demonstrated between variation in cranial shape and genetic distances estimated from the mtDNA and nuclear loci. Notably, B. ephippium and B. garbeana that are predicted to be sister-species in the individual and concatenated gene trees and the BEST species tree share an evolutionary novelty, the hyperossified dorsal plate. © 2011 Elsevier Inc.
Keywords: Amphibia; BEST; Brachycephalus; Brazil; Gene trees; Geometric morphometrics; Species tree; mitochondrial DNA; ribosome DNA; RNA 16S; animal; Bayes theorem; classification; DNA sequence; evolution; frogs and toads; genetics; histology; mitochondrion; molecular evolution; molecular genetics; multilocus sequence typing; nucleotide sequence; phenotype; phylogeny; skull; species difference; Animals; Anura; Base Sequence; Bayes Theorem; Biological Evolution; DNA, Mitochondrial; DNA, Ribosomal; Evolution, Molecular; Mitochondria; Molecular Sequence Data; Multilocus Sequence Typing; Phenotype; Phylogeny; RNA, Ribosomal, 16S; Sequence Analysis, DNA; Skull; Species Specificity; Brachycephalidae; Brachycephalus ephippium